THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON NURSES WORK PRODUCTIVITY - Juwita Ramadani Fitria (International Journal Management and Economic, 2023)
This study aimed to determine the effect of work discipline and work motivation on the productivity of nurses in the inpatient unit at RSIA Buah Hati Pamulang, either partially or simultaneously. The method used is quantitative. The sampling technique used the Slovin method, and the sample obtained in this study amounted to 55 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study show that Work Discipline and Work Motivation significantly affect Work Productivity with the regression equation Y = 9,600 + 0,382X1 + 0,385X2. The correlation value of 0.601 means that the independent and dependent variables have a strong relationship level. The value of the coefficient of determination is 36.1%, while other factors influence the remaining 63.9%. The hypothesis test obtained a value of F arithmetic > F table or (14,671 > 2,780). Thus, H0 is rejected, and H3 is accepted. This means there is a simultaneous significant influence between Work Discipline and Work Motivation on Work Productivity.